Fig 3 - - Yuan Yue (313562); HaiFeng Liu (11725991); XiuXiang Mu (11725994); MengSheng Qin (11725997); TingTing Wang (10276238); Qi Wang (22418); YaQiong Yan (11726000) (2021)
Spatial distributions for the trends of annual and seasonal SPEIs during 1970–2014: (a) annual; (b) spring; (c) summer; (d) autumn; (e) winter.